A qualitative systematic review on the lived experience of men in nursing - Xiaochen Lyu; Thitinut Akkadechanunt; Pratum Soivong; Phanida Juntasopeepun; Ratanawadee Chontawan (Wiley, 2022)
Abstract Aim This qualitative systematic review was conducted to describe the lived experience of men in nursing. Design A systematic review of qualitative studies. Methods Five databases (Scopus, CINAHL, MEDLINE, PsycINFO and Embase) were systematically searched. The PRISMA guideline was used for reporting the literature search in different phases, and the Critical Appraisal Skills Program, a qualitative research checklist, was used to evaluate the studies that met the inclusion criteria. Thomas and Harden's thematic analysis approach for qualitative research was used for data synthesis. Results Six qualitative studies were included. Five analytical themes related to lived experiences of men in nursing emerged: value in nursing, the double‐edged sword of gender, being accepted in the nursing profession, attractions of nursing and coping strategies.